2009
DOI: 10.1007/s00436-009-1691-7
|View full text |Cite
|
Sign up to set email alerts
|

Nucleotide sequence heterogeneity in the small subunit ribosomal RNA gene within Theileria equi from horses in Sudan

Abstract: This is a molecular epidemiological investigation on Theileria equi, a causative agent of equine piroplasmosis. Blood samples were collected from 127 horses from different geographical locations in Sudan. The small subunit of rRNA gene (18S; ~1,600 bp) was amplified from 20 positive field samples and subsequently subjected to direct sequencing and analysis to reveal possible strain differences and the presence of a novel species or genotypes. Sequences were compared with published sequences mainly from South A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
24
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(30 citation statements)
references
References 22 publications
4
24
0
2
Order By: Relevance
“…The high prevalence of T. equi we found in both equid populations is consistent with a South African study of Cape (Equus zebra zebra) and Plains zebras (Equus quagga burchelli), where the prevalence was 86% (95% CI 75.5-92.3%) (Bhoora et al 2010), although horses in Sudan and South Africa had lower prevalences (9.8% [95% CI 3.8-21.4%]) (Motloang and Thekisoe 2008;Salim et al 2010). Theileria equi is also common in donkey populations in tropical and subtropical countries including Brazil, India, the Arabian countries, and South Africa, although the prevalence is unknown (Kumar and Dwivsdi 2002).…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…The high prevalence of T. equi we found in both equid populations is consistent with a South African study of Cape (Equus zebra zebra) and Plains zebras (Equus quagga burchelli), where the prevalence was 86% (95% CI 75.5-92.3%) (Bhoora et al 2010), although horses in Sudan and South Africa had lower prevalences (9.8% [95% CI 3.8-21.4%]) (Motloang and Thekisoe 2008;Salim et al 2010). Theileria equi is also common in donkey populations in tropical and subtropical countries including Brazil, India, the Arabian countries, and South Africa, although the prevalence is unknown (Kumar and Dwivsdi 2002).…”
Section: Discussionsupporting
confidence: 75%
“…The phylogenetic tree (Fig. 2) shows two distinct clades with greater than 86% posterior probabilities to isolates from horses in four geographic areas within Sudan (Salim et al 2010). Three isolates were found in Atbara and one in El Obeid.…”
Section: Discussionmentioning
confidence: 99%
“…than has been previously reported. A similar study conducted in Sudan revealed the existence of nine distinct T. equi sequences in the region, which led to the identification of an additional, fourth T. equi genotype (Salim et al, 2010). While the sequence differences in most cases were minimal, the occurrence of previously unrecognized sequence variation could pose a potential problem in the implementation of the T. equi qPCR assay, as variation in the regions where the T. equi real-time primers and probe have been designed would render the assay non-specific.…”
Section: Discussionmentioning
confidence: 80%
“…First, we examined full-length 18S rRNA gene sequences to provide broad phylogenetic groupings for all samples into the four previously described clades of T. equi [21,25]. Next, we developed a panel of 18 microsatellite markers to provide finer-scale resolution of these genetic relationships.…”
Section: Introductionmentioning
confidence: 99%